What is Design for Meaning?. (1st October 2017) - Giacomin, Joseph
Considering the importance of meaning, it is perhaps surprising to note the frequent lack of clarity about the matter in the design literature and in design practice. Concepts such as value, ideology, meaning, function, ritual, myth and metaphor are often used interchangeably, with important consequences in terms of possible misunderstanding. A review of key concepts in the discussion of artefact meaning has been performed, and several considerations of relevance to commercially active designers have been identified. The reflections are summarized as a framework that provides a tool for identifying key questions that should be answered. As part of the process of defining the framework of design for meaning, the concept of 'meaningfication' was established. The potential usefulness of the proposed framework is noted in relation to recent developments in the areas of value creation, business and branding.